TIPOLOGI KERAMIK WADAH PORSELIN CINA (Studi Pada Keramik di Museum Provinsi Sulawesi Tenggara) - muhammad Zulfadly (SANGIA: Jurnal Penelitian Arkeologi, 2017)
This study examines variations in the shape and decorative motifs of Chinese porcelain container ceramics in the Southeast Sulawesi Provincial Museum. And the function of Chineseceramics in Tolaki people in Southeast Sulawesi. This research uses inductive reasoning methodthat is descriptive analytical. The stage of data collection is achieved through library studies andobservation / observation. In analyzing the data this study uses morphological analysis and stylisticanalysis. Based on the results of the study, there were 170 Chinese porcelain container ceramics inthe Southeast Sulawesi Provincial Museum consisting of plates, bowls, pots, jars and vases. Thevariations in the types of Chinese porcelain containers in the Southeast Sulawesi ProvincialMuseum are 13 types. Whereas there are 25 decorative motifs of Chinese porcelain containers inthe Southeast Sulawesi Provincial Museum consisting of 9 types of plates, 6 types of bowls, 5types of pots, 3 types of jars and 2 types of vases. There are two functions of Chinese ceramics fortolaki people in Southeast Sulawesi, namely; Social functions, namely as a daily necessity tool. TheFunction of Culture, namely as a ritual tool in the form of a container and stock of graves, as well asbeing used as a dowry.